PENGARUH ANALISIS FUNDAMENTAL DAN ANALISIS TEKNIKAL TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ45 - Christian Chandra Wijaya; Arie Pratania Putri (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
ABSTRACT This research aims to determine whether technical analysis and fundamental analysis have an influence on the price of shares, both partially and simultaneously. The population in this study is 45 companies listed as members of the LQ45 index. In sampling, researchers coordinate the purposive sampling method, sampling by consideration of some criteria. The data used in this study is the financial statements of the company acquired from the website www.idx.co.id and the official website of the company itself. The research methods used in this study are a descriptive analysis method and multiple linear regression analysis methods. The results of this study show that partial current ratio has no effect and is insignificant to the stock price, the price earning ratio is influential and significant towards the stock price, the trading volume is influential and not significant to the stock price, and the Indeks Harga Saham Gabungan has no effect and is significant to the stock price. Simultaneously the current ratio, price earning ratio, trading volume, and Indeks Harga Saham Gabungan are influential and significant to the stock price.